Investigation on mechanical properties of chicken feather fibers reinforced polymeric composites. (2021) - Vinodh kumar, S.; Prasanth, K.; Prashanth, M.; Prithivirajan, S.; Anil Kumar, P.
Abstract: The objective of this investigation is to utilize the poultry waste of chicken feather fibres into suitable applications and evaluate the mechanical properties. Chicken feather fiber reinforced (epoxy resin) composites were processed by hand layup method. In order to produce the composites, the chicken feather fibers (CFF) were processed with epoxy resins for three fiber reinforcement loadings. Different experimental investigations were conducted to determine mechanical properties of CFF reinforced composites.